Creative-interactive PAI strategies for generation z and society 5.0 vision - Shidikin, Eko Ngabdul; Ramadhan, Rudi Nur; Sepriadi; Hibatullah, Faiz Roisuddin; Haq, Muhammad Izzul; Triyono, Riyan (ATTARBIYAH: Journal of Islamic Culture and Education, 2025)
This study examines the use of creative–interactive Islamic Education (PAI) strategies through social projects in a junior high school context. The approach aims to internalize religious values, increase student engagement, and align learning with the human-centered principles of Society 5.0. An exploratory qualitative single-case study was conducted at SMP Muhammadiyah Panggang involving 11 participants (two teachers and nine students) selected through purposive maximum variation sampling. Data were obtained from interviews, observations, and learning artifacts, and were analyzed thematically with credibility ensured through member checking and an audit trail. The findings show that social projects shifted PAI learning from passive knowledge delivery to an action–reflection–meaning cycle. Students displayed strong participation, collaboration, creativity, and improved digital skills through poster production, slogan creation, and video documentation. The value “cleanliness is part of faith” was internalized and sustained in daily behavior. Teachers considered this strategy highly suitable for Generation Z and consistent with Society 5.0, although successful implementation requires coordination, adequate time, and standardized authentic assessment.